2000
DOI: 10.1038/sj.bjp.0703280
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of peroxynitrite in ischaemic preconditioning in rat isolated hearts

Abstract: 1 The aim of this study was to investigate the involvement of peroxynitrite, reactive metabolite originating from nitric oxide and superoxide, in preconditioning of the ischaemic myocardium in rat isolated hearts. 2 Isolated hearts perfused with Krebs-Henseleit solution were preconditioned either by 3 min of coronary artery occlusion (CAO) or by peroxynitrite administration at three dierent concentrations (0.1, 1, 10 mM) for 3 min, followed by 10 min reperfusion and 30 min of CAO. Peroxynitrite, at 1 mM concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 49 publications
5
59
0
2
Order By: Relevance
“…Further studies also confirmed that enhanced peroxynitrite formation plays a central role in numerous cardiovascular diseases by inducing oxidative, nitrative and nitrosative stress (Pacher et al, 2007). However, peroxynitrite was demonstrated to have physiological functions (Lefer et al, 1997) and to play a role in triggering ischaemic preconditioning (Altug et al, 2000;Altup et al, 2001;Csonka et al, 2001). We have previously reported for the first time that peroxynitrite is a trigger of IPost since the peroxynitrite scavenger, FeTPPS, interfered with the cardioprotective effect of IPost (Kupai et al, 2009 Beginning of ischaemia a 10.7 ± 1.0 9.0 ± 0.8 11.5 ± 1.0…”
Section: Figurementioning
confidence: 66%
See 1 more Smart Citation
“…Further studies also confirmed that enhanced peroxynitrite formation plays a central role in numerous cardiovascular diseases by inducing oxidative, nitrative and nitrosative stress (Pacher et al, 2007). However, peroxynitrite was demonstrated to have physiological functions (Lefer et al, 1997) and to play a role in triggering ischaemic preconditioning (Altug et al, 2000;Altup et al, 2001;Csonka et al, 2001). We have previously reported for the first time that peroxynitrite is a trigger of IPost since the peroxynitrite scavenger, FeTPPS, interfered with the cardioprotective effect of IPost (Kupai et al, 2009 Beginning of ischaemia a 10.7 ± 1.0 9.0 ± 0.8 11.5 ± 1.0…”
Section: Figurementioning
confidence: 66%
“…Increasing evidence suggests that enhanced formation of cardiac peroxynitrite is involved in cardioprotection afforded by both pre- (Altug et al, 2000;Altup et al, 2001;Csonka et al, 2001) and postconditioning (Kupai et al, 2009;Li et al, 2013). Kupai et al reported first that IPost failed to decrease infarct size in the presence of a peroxynitrite decomposition catalyst, thereby suggesting essential triggering role of peroxynitrite in postconditioninginduced cardioprotection (Kupai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, low concentrations of peroxynitrite, such as those produced in LPS preconditioning, can be beneficial to the ischemic brain. In the peripheral circulation, peroxynitrite improves endothelial function, protects the myocardium from injury, and can act as a preconditioning agent Nossuli et al, 1997;Altug et al, 2000). In the CNS, peroxynitrite is involved in LPS preconditioning against excitotoxic brain lesions .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PN, at low concentrations, may exert favorable effects in decreasing the incidence of ischemia/reperfusion-induced dysrhythmias [290]. Moreover, the use of a cell-permeant antioxidant that reacts rapidly with PN, abolished the beneficial effect of PN [296].…”
Section: Protective Effect Of Peroxynitrite In Ischemia Reperfusion Imentioning
confidence: 77%